Risk Mitigation and Mapping on Tubular System During Microbial Huff and Puff Injection Coupled with Lean Six Sigma Approach at Field X - Steven Chandra; Prasandi Abdul Aziz; Wijoyo Niti Daton; Muhammad Rizki Amrullah (Journal of Petroleum and Geothermal Technology, 2021)
Increasing demand of oil in Indonesia is in contrast with the decreasing oil production every year. Enhanced oil recovery (EOR) has become one of the most favorable method in maximizing the production of mature fields with various applications and research has been done on each type, especially microbial EOR (MEOR). “X” field is a mature oil field located in South Sumatra that has been actively producing for more than 80 years and currently implementing MEOR using huff and puff injection. However, there are some potential risks regarding MEOR processes that may inhibit the production by damaging the well’s tubular system, particularly microbially induced corrosion (MIC). This study reviews the risk mitigation and mapping to prevent corrosion on tubular system during MEOR huff and puff processes, equipped with the approach of Lean Six Sigma.The mitigation and mapping process follow the framework of define, measure, analyze, improve, and control (DMAIC). It starts with defining the problem using supplier-input-process-output-customer (SIPOC) diagram after all the field data necessary has already been collected, then measuring the corrosion rate model using ECE™ software as well as conducting sensitivity analysis of the fluid rates. The analyze phase involves constructing fishbone diagram to identify the root causes, comparison with industry’s specification and standard, and analysis of chromium effect on corrosion rates. Further simulation is conducted to support the analysis and to ensure the improvements and sustainability of the design selection.Based on the simulation results, the normal corrosion rate ranging from 0.0348 – 0.039 mm/year and the pH is around 4.03 – 5.25, while the ±30% fluid rate sensitivity results shown that the change of water flowrate is more sensitive than oil flowrate with the corrosion rate approximately 0.0275 – 0.048 mm/year. The fishbone diagram identifies that material selection and environmental condition as the main root causes, then corrosion resistant alloy (CRA) is used in the tubing string to prevent corrosion in the future by using super 13Cr martensitic steel (modified 2Ni-5Mo-13Cr) as the most suitable material. Further simulation on chromium content supports the selection that corrosion rate can be reduced by adding the chromium content in the steel. The completion design is then capped with choosing the Aflas® 100S/100H fluoro-elastomer as the optimum material for packer and sealing. Overall, the Lean Six Sigma approach has been successfully applied to help the analysis in this study.